Дослідження селекційного матеріалу рижію посівного (Camelina sativa (L.) Crantz) за допомогою ISSR-аналізу - Баєр, Г.Я.; Бойчук, Ю.М.; Пірко, Я.В.; Корховий, В.І.; Рахметов, Д.Б.; Ємець, А.І.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2014)
Aims. The aim of investigation is the applicability of ISSR markers for uncovering polymorphism to study the relationships between C. sativa genotypes. Methods. Twelve genotypes were analyzed using seven primers. Extracted DNA was successfully used for study by ISSR-PCR method. The genetic distances were used to construct the UPGMA dendrogram which characterized relationships between studied genotypes. Results. The level of genetic polymorphism of C. sativa is 76.5%. The unique fragments have been revealed in 6 genotypes. The studied genotypes were divided in two clusters. Conclusions. It was shown that ISSR analysis is the useful method for fingerprinting and determination of relationships between the different C. sativa genotypes. The results can be used in breeding programs for the genetic identification of cultivars for copyright protection and to control the spread of promising breeding material.